BIM-FM and Consequential Loss: how consequential can design models be? - Olatunji, Oluwole (Emerald Group Publishing, 2014)
Purpose: BIM offers a new direction of project implementation. It promotes integration of multiple lifecycle stages as well as multidisciplinary integration; whereas conventional approaches are primed on fragmentation. This study adds to existing debates on the relationship between the rationality of the legal structures underlying fragmented project delivery and BIM’s ability to successfully foster integration across different lifecycle stages. A step further from extant arguments on whether BIM could be sufficiently serviced by the same legal provisions that had serviced fragmented relationships, the study opens up some new fronts regarding the consequences of shared trusts and reciprocity in an integrated project platform. As a way to strengthen interdependencies across multiple lifecycle stages, the study raised certain questions that trigger further studies. Approach: In addition to a deep analysis of traditional literature on BIM and project management, the study draws its strength from two recent court cases on the limitations of disclaimers against liable breaches. It also targets court decisions on consequential loss and the duty of care to explain project team’s liabilities when BIM could not live to its theorized promises. Findings: The study shows that disclaimers are a weak protection against liabilities. As BIM offers a dynamic project environment, the study relies on decided cases to show that duty of care to a project (and its owners) is not entirely representable by prototype contract language. More importantly, the study concludes that the applications of BIM to FM are better supported on BIM’s new dimension of multidisciplinary integration, rather than a mere coalescing of deliverables across different lifecycle fragments. Originality/value: This work is neither published nor under consideration for publication elsewhere. It adds to the growing debates on the legal implications of BIM by looking at the potential of digital models as a valid and admissible contract instrument.